Design Thinking and Computational Thinking and their articulations for the Educational Robotics teaching: a review - Rosa, Valdir (2020)
This paper examines the growing field of using design thinking and computational thinking for teaching educational robotics through a mapping based in the systematic literature review steps. This mapping gathers evidence of how the robotics teaching has become a useful tool for the development of cognitive abilities, and such as computational thinking, being further enhanced by the use of design thinking. In this sense, it was sought in the literature to know how these approaches are being evaluated, at what levels of education are being carried out in this area of studies, if there is a curriculum formulated for this purpose, and what results have already been achieved. The consequences, study point to an increasing use of educational robotics for the development of computational thinking, being carried out at all levels of education in Basic Education. There isn´t fully defined curriculum and nor a standard to be followed, but there are contributions implicit design thinking in the activities reported for the development of computational thinking.